PENGGUNAAN MEDIA CARD KINGDOM HISTORY MELALUI METODE KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Karlina, Nindi; Gusrayani, Diah; Kurnia, Dadang (Jurnal Pena Ilmiah, 2017)
Based on the observations made on the IPS learning material heyday and the heritage of Islam Nusantara in grade V SDN Gunasari Sumedang Regency is known that the ability of students on historical material is still low. The problems that occur because of the difficulty of memorizing abstract historical material. Efforts are made to overcome the problem is with the use of Card Kingdom History through cooperative STAD type method. The purpose of this study is to improve student learning outcomes in the material heyday and archaeological history of Islam Nusantara and increase student activity on aspects of cooperation. The research used is Classroom Action Research (PTK) with Kemmis and Mc Taggart model. After 3 cycles, there was a significant improvement so that the use of Card Kingdom History through cooperative method of Student Team Achievement Divisions has improved the students' learning achievement of grade V of SDN Gunasari Sumedang Regency on the material of heyday and the archaeological history of Islam Nusantara